ENT 300 : Paradise Found Real Estate / Siti Faridah Amin ... [et al.] - Amin, Siti Faridah; Dominic, Ouzza Ndy; Abd Razak, Raimalynah; Sanin, Sharmiza; Laoding, Hasnimulyati (2011)
Paradise Found Real Estate offers to be the seller's or buyer's agent in the process of buying and selling properties, acting as an intermediate in searching what the client's want specifically. Our clients are the citizens of Kota Kinabalu which is included in the age range from 25 years old to 74 years old with middle income range. Paradise Found Real Estate offers a variety of real estate services from representing clients in buying and selling properties, assisting buyers in searching for available property and also advertizing seller's property to potential buyers and agents. Across Sabah the real estate business has seen an increasing of growth over the years. Kota Kinabalu is an affluent area with a high population density throughout Sabah. While there are currently five businesses offering real estate in Kota Kinabalu, only three of these has website and none operates in Alamesra, Kota Kinabalu Industrial Park. Paradise Found Real Estate's marketing strategy is to emphasize the client's trust ("Your Trust is Our Priority.") and the availability of our services. Citizens who work, for instance, will come home to find out that their property has been sold to a potential buyer All real estate services will be provided by appointed agents. On startup we will have five trained agents to provide real estate services and expect to hire five more after three years once financing is secured. To begin with, we hire a full-time receptionist this year as well that will be scheduling appointments and coordinating services. The management of Paradise Found Real Estate consists of partners Siti Faridah Amin. Ouzza NDY Dominic, Raimalynah Abd Razak, Sharmiza Sanin and Hasnimulyati Laoding. All partners will be taking hands-on management roles in the company. Based on the size of our market and our defined market area, our sales projections for the first year are RM250. 000. We are seeking an operating line of RM42. 000 to finance our first year growth. Together, the partners have invested RM25 000 to meet working capital requirements. We plan to aggressively build our client base through poster, flyers, business cards, signboard, website, Facebook fan page, email and opening ceremony. The real estate service that Paradise Found Real Estate will provide is sure to appeal to clients throughout the Kota Kinabalu area.